Identifikasi Arsitektur Bioklimatik pada Relokasi Pasar Tradisional Antang di Kota Makassar - Massarappi, A. Mughny A.; Rahayu, Irma; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2025)
Conventional markets, which serve as economic and social spaces for urban communities, face problems such as declining physical quality, thermal comfort, and spatial order. Antang Traditional Market in Makassar City appears very crowded and disorganized, and is unable to adapt to the humid tropical climate. The purpose of this article is to create a more comfortable, healthy, and sustainable traditional market by relocating and redesigning Antang traditional market using a bioclimatic architecture approach. A descriptive qualitative design-oriented method (research by design) was used to collect primary data (site and building observations, vendor-visitor activity surveys, documentation of microclimate conditions) and secondary data (population data, spatial planning, and literature on markets and bioclimatic architecture). Site analysis, activity-space needs survey, and bioclimatic analysis are the stages used to develop and confirm the criteria. The result is a new market design that utilizes building orientation, wind corridors, openings and skylights, shading systems, vegetation, and hollow brick facade details to improve ventilation and natural lighting. The open, porous interior and exterior design enhance thermal and visual comfort while reinforcing the market's climate-friendly identity.